Impact of personal experience on artistic creation by Chinese film directors in cross-cultural communication - Li, Jiangyue; Muhammad Hakimi Tew Abdullah; Wan Hartini Wan Zainodin (Penerbit Universiti Kebangsaan Malaysia, 2025)
This research explores how Chinese film directors' personal experiences influence their artistic creation, particularly in cross-cultural communication. Drawing from cultural heritage, life journey, and professional encounter, directors infuse their work with authenticity, emotional depth, and innovative storytelling. Key themes identified include artistic expression, cross-cultural influence, literary inspiration, and strong character development, contributing to film resonance locally and globally. With qualitative methodology, in-depth interviews were conducted on 25 directors selected through purposive sampling. Thematic analysis with NVivo software identified patterns in their creative process, thematic choice, and strategy for engaging global audience. Interpretative phenomenological analysis (IPA) applied open, axial, and selective coding until data saturation was reached. Ten key themes emerged: Artistic Expression, Authenticity, Interplay of Chinese & Western Cultures, Emotion & Experience, Literary Inspiration, Knowledge & Background, Optimistic Perspective, Creative Phase, Strong Character, and Film Creation Theme. Findings highlight the pivotal role of personal experience in shaping artistic vision, emphasizing resilience, cultural identity, and emotional storytelling. Directors balance traditional Chinese aesthetics with modern technique, fostering cross-cultural dialogue and global understanding. This paper underscores how personal authenticity and cultural heritage enrich filmmaking, enhancing Chinese cinema’s global appeal while preserving its unique identity. It provides valuable insight into the significance of Chinese cinema and a deeper understanding of filmmakers’ motivation and creative intention.